PERKEMBANGAN PONDOK PESANTREN NURUL IMAN KECAMATAN SITIUNG, KABUPATEN DHARMASRAYA TAHUN 1999-2013 - Yulia, Itra - (Pendidikan Sejarah, 2014)
Â Thesis is about. Thesis is development of Nurul !man koranic School at Dharrnasraya Regancy since 1999 un til2013. The main Problem are about history, condition, developm ent, and many factors that influence the Development of Nuru l lman koranic school. Gera lly, the purpose of this research is to reveal the Development of education at Nurul lman koronic school since 1999 until 2013, While especially, the purpose of this research is to describe th e development ofNurul!man koroni c school since 1999 until 20 13. The method of t his research is history method with using some steps as like as heuristicis collectin g the data. Resource critic is testing the data . Resource critic is testing the data. Interpretation is understanding and explaining the information, then Historiography is writing process of gett ing th e result of this research in scientific paperor thesis. The result of this research are Nurul Iman koranik school that standing by Buya Abbas on September 19 th 1999 has some purposes such as educate the children and expand the muslim personality, that is faith ful personality and piety to Allah, have a certain character, useful In society and dependable in persona lity with maintain the Islam. In 1999 until 2000 Nurul lman koran ic sch ool consisted of Student s in 199912000, in 2000/200 I it consisted of 138 students, in 200112002 it consisted of 198 students, in 2002/2003 it consisted of 2 17, and in 2003/2004 it consisted of 20 I students. Every year, the students are always increasing in Nu ru l Iman koranic school. Based on the result of this research, it can beconcluded that Buya Rijal Abbas has good desire to build thi s Nurul !man koranic school. It can be seen by buildin g Islam Junior school and Islam Senior school , so Nurul lman koranik sch ool should be support ed by Religion ministry, society, and Leader ofNurullmanÂ  koranic school.Â